2018
DOI: 10.3390/met8020126
|View full text |Cite
|
Sign up to set email alerts
|

Slurry Erosion Behavior of AlxCoCrFeNiTi0.5 High-Entropy Alloy Coatings Fabricated by Laser Cladding

Abstract: High-entropy alloys (HEAs) have gained extensive attention due to their excellent properties and the related scientific value in the last decade. In this work, Al x CoCrFeNiTi 0.5 HEA coatings (x: molar ratio, x = 1.0, 1.5, 2.0, and 2.5) were fabricated on Q345 steel substrate by laser-cladding process to develop a practical protection technology for fluid machines. The effect of Al content on their phase evolution, microstructure, and slurry erosion performance of the HEA coatings was studied. The Al x CoCrFe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Zhao et al [127] conducted their research work on the slurry erosion behavior of laser cladding-made highentropy alloy (HEA) coatings. AlCoCrFeNiTi 0.5 HEA coating exhibited excellent slurry erosion prevention at different impingement angles due to its elevated hardness, excellent plasticity and low stacking fault energy.…”
Section: Studies Related To Slurry Erosion Prevention Using Laser Clamentioning
confidence: 99%
“…Zhao et al [127] conducted their research work on the slurry erosion behavior of laser cladding-made highentropy alloy (HEA) coatings. AlCoCrFeNiTi 0.5 HEA coating exhibited excellent slurry erosion prevention at different impingement angles due to its elevated hardness, excellent plasticity and low stacking fault energy.…”
Section: Studies Related To Slurry Erosion Prevention Using Laser Clamentioning
confidence: 99%
“…Kunce et al [211] demonstrated that thin-walled structures of highentropy alloys (HEAs) AlCoCrFeNi could be fabricated with LENS technology. They demonstrated that laser scanning speed has a significant effect on microstructure and hardness of fabricated thin-walled element and also demonstrated that increasing the cooling rate during the solidification process reduced the average grain size of alloy [211,212]. WAAM has been described as a low-cost method for the fabrication of large-scale thin-walled structures by expressively decreasing product development time and "buy-to-fly" ratios to the aerospace manufacturing industry [213,214].…”
Section: Thin-walled Parts Qualificationmentioning
confidence: 99%
“…In eutectic high entropy alloy (EHEA), if the lamellar eutectic structure is composed of the phase with high hardness and the phase with good toughness, the slurry erosion resistance will be greatly enhanced. Zhao et al [10] reported that the Al 1.0 CoCrFeNiTi 0.5 HEA is composed of simple FCC phase and BBC phase, and its erosion rate is 1.73 times lower than Cr16 alloy. Wu et al [11] reported that with the increase in the aluminum content in Al x CoCrCuFeNi alloys, both the BCC phase proportion and the hardness value increase.…”
Section: Introductionmentioning
confidence: 99%